Implementasi Model Pembelajaran Berbasis Proyek untuk Meningkatkan Hasil Menulis Prosa Fiksi Mahasiswa Program Studi Sastra Indonesia Universitas Jambi - Wilyanti, Liza Septa; Wulandari, Sovia; Izar, Julisah (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The aim of this research is to enhance the activity and skills of pre-writers of fiction prose using a project-based learning model in the Indonesian Literature program at the Faculty of Education and Teacher Training, Universitas Jambi. The research method employed is Classroom Action Research (CAR) conducted in two cycles. Each cycle involves planning, implementation, observation, and reflection stages. Data are analyzed according to the assessment rubric. In Cycle I, there was an improvement in activity levels, with 87% of students achieving a good category and 13% achieving a very good category. The improvement in pre-writing scores was 60%, reaching a sufficient category for 40% and a good category for 40%. However, the analysis indicated that the target of exceeding 50% of pre-writing scores in the good category was not achieved in Cycle I, prompting the continuation to Cycle II. In Cycle II, both activity and pre-writing scores experienced significant improvement. Activity scores showed 33.3% of students in the good category and 86.7% in the very good category. Pre-writing scores increased to 33.3% in the good category and 66.7% in the very good category. Based on the research findings, it can be concluded that the implementation of the Project-Based Learning model in the Fiction Prose Writing course effectively enhances the activity and skills of pre-writers of fiction prose and is deemed suitable for application